Manger à l’œil : quand l’exposition donne à voir le repas des Français - Julie Deramond; Laure Marchis-Mouren (In Situ)
The exhibition entitled ‘Manger à l’oeil’ in French (meaning to get a free meal) and called ‘Say cheese!’ in English was presented at the Museum of European and Mediterranean Civilisations (MuCEM), in Marseilles, from 20 July to 30 September 2018. It told the story, in pictures, of two hundred years of table practices in France. It reported on the evolution of the gastronomic meal of the French which was put on UNESCO’s representative list of the intangible cultural heritage in 2010. Photography, as a medium, was chosen for its ability to capture the present moment and to highlight changes in ways of consuming. The MuCEM exhibition is analysed here from a communicational point of view, based on information and communication sciences and museology. The exhibition suggests a definition of the French gastronomic meal as a unifying and evolving phenomenon, intimately linked to social changes. The aesthetic form of the exhibition, including its scenography and the choice of the objects presented, contributes to legitimising the identification of the French gastronomic meal as heritage for a large audience. This consensual exhibition plays its part in an overall policy of promoting the food heritage.